IDENTIFY THE RISK FACTORS THAT CAUSE THE MAJORITY OF DEATHS IN ICU PATIENTS OF PAK ITALIAN BURN CENTRE, NMU, MULTAN - NUSRAT , .; NISA , QU; JAMSHAID , A; NAZ , S (Biological and Clinical Sciences Research Journal, 2024)
Burn injuries represent a significant public health challenge in low- and middle-income countries, including Pakistan, with high mortality rates in intensive care units (ICUs) due to delayed access to care, extensive burns, and comorbid conditions. Understanding the factors contributing to mortality is crucial for improving patient outcomes. Objective: To evaluate the factors influencing ICU mortality among burn patients at the Pak Italian Burn Centre, Nishtar Medical University and Hospital, Multan. Methods: A descriptive cross-sectional study was conducted among 130 ICU burn patients aged 18 years and above, admitted with ≥20% total body surface area (TBSA) burns. Data on demographics, clinical characteristics, comorbidities, and outcomes were collected using a structured proforma. Mortality was analyzed as the primary outcome, with associations assessed using SPSS version 26. Chi-square tests and logistic regression analyses were used to identify significant predictors of mortality. Results: The overall ICU mortality rate was 48.5%. TBSA >40% was a significant predictor of mortality, with 77.8% of these patients succumbing to their injuries (p<0.001). Inhalation injuries were present in 30.8% of patients, contributing to a 70% mortality rate (p<0.01). Comorbidities such as diabetes (62.5% mortality) and hypertension (71.4% mortality) were significantly associated with poorer outcomes (p<0.05). Age ≥65 years further increases mortality risk. Full-thickness burns and delayed presentation also correlated with worse outcomes. Conclusion: High mortality rates among burn ICU patients in Pakistan are primarily driven by extensive burns, inhalation injuries, and comorbid conditions. These findings emphasize the need for early interventions, comprehensive care, and improved healthcare infrastructure to enhance survival outcomes in resource-limited settings.